1987
DOI: 10.1080/03746608708685418
|View full text |Cite
|
Sign up to set email alerts
|

Man and mire: a long and wet relationship

Abstract: Several different types of mire, that is peat-forming ecosystem, contain in their stratigraphic and pollen record evidence of human activity. Often this coincides with either the commencement of peat formation or a major change in the type of peat being formed. Some mires can therefore be regarded as man-made habitats. Examples are discussed which include valley mires in southern Spain and in England, a schwingmoor in central Wales, and the blanket mires of upland and western Britain. All of these show major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In Scotland, this theme was developed by a leading archaeologist, Stuart Piggott, into the idea that farming communities created blanket peat, albeit unwittingly, thus sowing the seeds of their destruction as blanket peat then spread remorselessly over their Welds (Piggott 1972). This idea is embedded also in the analyses of Peter Moore (Moore 1987(Moore , 1988(Moore , 1993 who argued that paludiWcation is an accidental by-product of destabilising the water balance of hill-slopes by farming, through woodland clearance, burning, cultivation or grazing. …”
Section: Introductionmentioning
confidence: 93%
“…In Scotland, this theme was developed by a leading archaeologist, Stuart Piggott, into the idea that farming communities created blanket peat, albeit unwittingly, thus sowing the seeds of their destruction as blanket peat then spread remorselessly over their Welds (Piggott 1972). This idea is embedded also in the analyses of Peter Moore (Moore 1987(Moore , 1988(Moore , 1993 who argued that paludiWcation is an accidental by-product of destabilising the water balance of hill-slopes by farming, through woodland clearance, burning, cultivation or grazing. …”
Section: Introductionmentioning
confidence: 93%
“…Topogenous mires of this type are found throughout the cool temperate and even into the warm temperate regions, especially at high elevation. Their initiation has occasionally been linked to human modification of valley soils, usually as a result of burning vegetation, erosion and the blocking of soil drainage properties by transported small carbon particles (Moore 1987). Topogenous mires are also found in the southern hemisphere, such as the buttongrass plains of Tasmania and the Restionaceae-dominated bogs of New Zealand (Campbell 1983).…”
Section: Types Of Peatlandmentioning
confidence: 99%
“…The development of alkaline fens is basically a natural process, and many fens probably started in the early Holocene (Dobrowolski et al, 2019; Grootjans et al, 2015; Kossler and Strahl, 2011; van der Hammen and Wijmstra, 1971; Van Geel et al, 1980). Human influence on the origin of fens and peat growth is usually low, although some authors (Czerwiński et al, 2021; Lamentowicz et al, 2013; Moore, 1987) concluded that some mires can be regarded as man-made habitats. Anthropogenic deforestation in the early Middle Ages locally led to increased groundwater discharge and often resulted in the development of alkaline fens (Grootjans et al, 2021), sometimes even in a former Sphagnum fuscum bog (Hájková et al, 2012).…”
Section: Introductionmentioning
confidence: 99%